Ludzas reliģiskās draudzes un baznīcas (1944-1991) - Liepiņa, Inese (Latvijas Universitāte, 2013)
Bakalaura darba mērķis ir izpētīt Ludzas reliģiskās draudzes un baznīcas, kā arī valsts institūciju ietekmi uz to darbību no 1944. – 1991. gadam. Hronoloģiskās robežas iezīmē komunistiskā režīma sākumu un beigas Latvijā. Pētījuma gaitā noskaidrojās, ka Baznīca spēja rast kompromisus ar padomju varu, panākot reliģisko organizāciju un ateistiskās politikas līdzāspastāvēšanu. Ludzas reliģiskās draudzes un baznīcas (Romas katoļu, pareizticīgo, Mozus ticīgo, luterāņu un vecticībnieku) ataino aktivitāšu saskaņošanu gan ar pilsētas izpildkomiteju, gan Reliģijas kulta lietu padomes pilnvaroto pie Latvijas PSR Ministru padomes. Ateisma propagandas ietvaros reliģisko draudžu dzīve koncentrējās tikai to lokā.

The main task for this bachelor thesis is to study the religical parishes and churches of Ludza, the influence of an institutions of the state to their activities during 1944 to 1991. The chronological borders shows the beggining and the end of the Communist’s regime in Latvia. During the studying of the thesis, it cleared that the Church found out the compromises with the Soviet power, gaining the coexistence of the religical organisations and atheistic politics. The religical parishes of Ludza ( Roman catholics, orthodoxy, Evangelical lutherans, believers of Moses, old believers) shows their activities with the executive committee of Ludza and the principal of council of Religical cult cases to Latvia’s SSR council of Minister. Living in the conditions of the atheistic propaganda, the life of the religical parishes mostly were spreaded only inside of parishes.
The religical parishes and churches of Ludza town during the years from 1944 to 1991
Keywords: Vēsture